SOLUSI UKHUWWAH ISLAMIYAH TERHADAP PROBLEMATIKA DAKWAH - Akhirudin, Akhirudin (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
Doctrinally ukhuwah Islamiyah is a steel bond that unites the Muslims. But the social reality shows that the steel bond has begun to rust, which makes the ummah no longer feel brothers. Through the title discussion Ukhuwwah Islamiyah as the problem of dakwah, want to be mapped problematic why it can happen. It can not be denied that political aspirations are very fragile to make the people divisive. The experience of everyday life in political culture shows it visibly. Let alone accept the defeat in the political arena even that happens is to make a political party match by forming a new party. Presumably the da'wah approach which is full of peace and softness should be disseminated so that the Ukhuwwah Islamiyah steel bond can be manifested by concrete and real